AN ANALYSIS OF DEIXIS USED BY STEVE HARVEY’S ON YOUTUBE CHANNEL - Susi Era Veri Lumban Gaol; Fenty Debora Napitupulu; Harpen Silitonga; Bangun Munthe (Jurnal Scientia, 2023)
This research deals with an analysis of deixis used by Steve Harvey on YouTube channels based on Yule’s theory. The objectives of this research are to identify the types of deixis used by Steve and the guest on Steve’s TV Show on the YouTube channel video and to identify how the use of deixis affects the meaning of the whole utterances of Steve and the guest. The data of this research is the utterance of Steve and the guest that contains Deixis. In this research, the writer analyzed the deixis found in the videos "Childhood Sweethearts Reunite 50 Years Later" and "15 Years Old Wig Designer Is Changing Lives." The video was taken from Steve TV Show’s YouTube channel. This research used descriptive qualitative research. In this research, the instrument of collecting data is observation and documentation. The result of this research shows that on the “Steve TV Show” YouTube Channel there is a total of 316 deixis. They categorized as person deixis is 231 data, spatial deixis is 47 data, and temporal deixis is 38 data. The use of the deixis in the conversation refers to various references depending on the context of the conversation. Moreover, the use of deixis helps the hearer avoid ambiguity and misunderstanding about the utterance